Analisis Risiko Lingkungan Rantai Pasok pada Agroindustri Kopi Robusta (Studi Kasus di Perumda Perkebunan Kahyangan Jember) - Dian Rahmatullah (Fakultas Teknologi Pertanian, 2025)
The robusta coffee agroindustry is an important sector in Indonesia's economy, with production estimated to reach 789 thousand tons in 2024. However, the growth of this industry poses environmental challenges, as approximately 40% of carbon emissions in the agroindustry sector come from supply chain activities such as transportation, processing, and waste disposal. This study aims to identify and analyze environmental risks in the supply chain of robusta coffee at Perumda Perkebunan Kahyangan Jember and to formulate effective risk mitigation strategies. The House of Risk (HOR) method is used to systematically identify potential environmental risks and risk sources throughout the supply chain, from planting to marketing robusta coffee. The identification results show nine potential risk events and sixteen risk sources, with five priority risk sources, such as wastewater from fermentation and the use of fossil fuels in drying and roasting machines. These risks directly contribute to water and air pollution. The study recommends two main mitigation strategies: the construction of Wastewater Treatment Installations (IPAL) to manage liquid waste and the installation of Wet Scrubber technology on processing machines to reduce dust and harmful gas emissions, thereby improving environmental quality and worker health. Environmental risk analysis using the HOR approach is effective in identifying and prioritizing risks in the robusta coffee supply chain, and the proposed mitigation strategies can support sustainability and environmental responsibility in this coffee industry
Reaploud Reposiotry February 2026_Hasyim
Keywords: Supply Chain Management; House Of Risk (HOR); Robusta Coffe